Effectiveness of Ayah 3A (Asih Asuh Anak) as a Supportive Media for Parenting to Improve Family Mental Health - Tiara Diah Sosialita (UM Purwokerto Press, 2021)
This study describes the effectiveness of the “Father 3A (Asih Asuh Anak)” program to support online parenting to improve family mental health. Sixty participants were involved, namely fathers of children and adolescents aged 7-18 years in densely populated areas. Information was sent as text messages via Short Message Service (SMS) or WhatsApp (WA). This study was conducted to solve the community’s need for online tools that support family mental health. The method of the “Ayah 3A” program was sending some messages about parent-child attachments, co-parenting, and daily self-care which were sent at a scheduled time. The shared material was adapted from theoretical concepts and previous studies’ findings. Besides provided online material, face-to-face meetings were also held for consultation sessions with psychologists. The effectiveness of this program was evaluated by a questionnaire of parenting skills and mental health. Meanwhile, evaluation of program implementation showed that 86% of the whole sample (n = 52) returned post-intervention questionnaires, and 66% of subjects followed this program completely. The results revealed that it was improving in knowledge and skill of parenting (p = 0.035; ES = 3.86) and mental health (p = 0.012; ES = 1.85). Besides, feedback evaluation from participants both quantitative and qualitative, regarding this program was quite effective.